Handbook of Famine, Starvation, and Nutrient Deprivation 2017
DOI: 10.1007/978-3-319-40007-5_90-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship Between Zinc Deficiency, Androgen Disorders, and Lung

Abstract: This review is focused on the adult lung in health and disease and the effect of zinc on both states. Pulmonary fibrosis (PF), chronic obstructive pulmonary disease (COPD), and asthma are some of the major health problems in the world. Zn is present in protein-bound and ionic forms, and plays important roles in mediating the function and structure of proteins, and in maintaining

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Besides, it has been reported that disruption of LH and FSH production and secretion in females and zinc deficiency led to abnormal ovaries, decreased estrogen secretion, and thus a disturbed estrous cycle [23]. The underlying mechanism behind the effects of zinc on the female reproductive system is probably based on the relationship between zinc and hormone receptors [24]. The sex hormones secreted by the female reproductive system bind to their specific receptors [23].…”
Section: Estrogen Concentrationmentioning
confidence: 99%
“…Besides, it has been reported that disruption of LH and FSH production and secretion in females and zinc deficiency led to abnormal ovaries, decreased estrogen secretion, and thus a disturbed estrous cycle [23]. The underlying mechanism behind the effects of zinc on the female reproductive system is probably based on the relationship between zinc and hormone receptors [24]. The sex hormones secreted by the female reproductive system bind to their specific receptors [23].…”
Section: Estrogen Concentrationmentioning
confidence: 99%